Processing, Microstructure and Mechanical Properties of Multi-layer Friction Surfacing in 7075 Aluminium Alloy - Matthieu, Jadot; Li, Jishuai; Gautier, Romain; Lezaack, Matthieu Baudouin; Sapanathan, Thaneshan; Simar, Aude (2024)
The solid-state AM process of Multi-Layer Friction Surfacing (MLFS) of high strength aluminium alloy 7075 leads to microstructure (grain size and precipitates size and distribution) and mechanical heterogeneities. The mean grain size at the bottom and top of a given layer is finer than at the middle of that layer. The strengthening precipitates are significantly affected by the layered structure due to the complex thermal field. These microstructural heterogeneities are affected by the thermal cycles experienced by the aluminium alloy 7075. The precipitates size gradient along the thickness of the deposit causes the significantly higher microhardness of the top layer. Post-deposition heat treatments are used to restore the uniformly T6 state microhardness. Although the part reveals some abnormal grain growth after the T6 heat treatment, tensile testing exhibits a strength above 500MPa and an elongation of typically 10%.